Evaluation of the Role of Internal Verification Doctors in Reducing Pending Claims at Murni Teguh Medan Hospital in 2022 - Sri Lestari Ramadhani Nasution; Yohana Candra Andini Hutabarat; Chrismis Novalinda Ginting (Jurnal Penelitian Pendidikan IPA, 2023)
In the claim verification process, errors are still encountered which cause the claim to be pending. The problem of pending claims that occurs causes many losses for the Hospital. Therefore, an internal verifier is needed to supervise claim verification so that problems with pending claims can be minimized. Internal verification doctors have an important task in reducing the number of pending claims, especially to control the suitability of coding with diagnoses on medical resumes. The aim of this research is to analyze and describe the contribution of internal verifier doctors in reducing pending claims as well as the factors that cause pending claims and claims coding errors. The type of research used in this research is qualitative research. The research design used in this research is a descriptive research design. This research has sources as key informants, namely 4 internal verification doctors. This research also has sources as supporting informants, namely coder representatives. The conclusions of this research are: (1). Factors causing pending claims at RSU Murni Teguh Medan include: (a). Administrative factors, (b). Coding factors, (c). Medical factors. (2). The factors that cause errors in coding claims at RSU Murni Teguh Medan include: (a). HR Factors (Natural Resources) and; (b). Disagreement factor. The role of the internal verifier doctor in reducing pending claims includes: (a). Medical Document Examination; (b). In-Depth Clinical Verification; (c). Collaboration with the Filing Team; (d). Communication with BPJS.